Evaluation of impact strength of heat cure and chemical cure acrylic resin denture base material - Ahmed Saleh Hamadameen (Erbil Dental Journal)
Background and Objective: Thermal and self-curing acrylic resins are widely used in dentistry because they are biocompatible, have no flavour or odour, have good thermal properties and polishing capacity, and are simple and quick to apply. As a result of its widespread use, fracture-resistant behaviour is particularly significant. We investigated the fracture resistance capabilities of thermal and self-curing acrylic resins in vitro in this study. The aim was to compare the impact strength between hot cure acrylic and cold cure acrylic. Method: 16 prosthetic specimens were made for each of the heat-cured and coldcured acrylic resins which were stroked and tested with a Charpy type digital impact tester (Electric Charpy impact tester) were used, and two joules of power were struck to get the fracture. Result: Although the difference was not statistically significant, during evaluation on average thermosetting resins were more resistant to fracture than self-curable resins. Conclusion: The outcome of this study concluded that the Heat-cured acrylic resins were, on average, more resistant to fracture than cold-cure acrylic resins, although the difference was not statistically significant.